2021
DOI: 10.3390/su13031147
|View full text |Cite
|
Sign up to set email alerts
|

Green Agricultural Development Based on Information Communication Technology and the Panel Space Measurement Model

Abstract: This study was conducted to promote the construction of China’s ecological civilization; to reduce harm to the environment; to quantify the performance of agricultural green development (GD); and to truly achieve green, sustainable, and healthy agricultural development. From the perspectives of resources and the environment, first, information communication technology and the panel space measurement (PSM) model were adopted to analyze relevant indicator data from 2000 to 2019 in China’s 30 provinces. Second, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Liu et al (2022) described agricultural green development as a comprehensive undertaking that encompasses six aspects: the greenization of the entire process, including agricultural production layout, resource utilization, technological means, industrial systems, agricultural product supply, and consumption [21]. Zhang et al (2021) defined agricultural green development as a process that respects natural laws, utilizes advanced scientific and technological means, explores sustainable agricultural development, and achieves the harmonious integration of economic, social, and ecological benefits [22]. perceived agricultural green development as a new development concept that aims to undertake sustainable development, relies on the establishment of green institutions and innovative mechanisms, and realizes the greenization of the entire process and all aspects of agricultural production [23].…”
Section: Research On the Connotation Of Agricultural Green Developmentmentioning
confidence: 99%
“…Liu et al (2022) described agricultural green development as a comprehensive undertaking that encompasses six aspects: the greenization of the entire process, including agricultural production layout, resource utilization, technological means, industrial systems, agricultural product supply, and consumption [21]. Zhang et al (2021) defined agricultural green development as a process that respects natural laws, utilizes advanced scientific and technological means, explores sustainable agricultural development, and achieves the harmonious integration of economic, social, and ecological benefits [22]. perceived agricultural green development as a new development concept that aims to undertake sustainable development, relies on the establishment of green institutions and innovative mechanisms, and realizes the greenization of the entire process and all aspects of agricultural production [23].…”
Section: Research On the Connotation Of Agricultural Green Developmentmentioning
confidence: 99%
“…Under the premise of determining how to measure agricultural green development in China, existing studies have analyzed its level and characteristics. For example, Zhang and Chen [ 25 ] found that the overall level of agricultural green development was steadily increasing. Deng et al [ 26 ] argued that its level shows a trend of rising first and then falling.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…Then, Paroussos et al (2020) explored Italian green growth and identified that renewable power innovation reduces the total factor CO 2 performance index. As an improvement or innovation of agricultural technology , the advancement of green agricultural technology can favor the development of green technologies for energy conservation and cleaner production and increase the marginal output of green agricultural products (Zhang and Chen, 2021). Ge et al (2022) found technological advancement through research on pig breeding.…”
Section: Literature Reviewmentioning
confidence: 99%